TEACHERS INITIATIVE TOWARDS PEACE AND VALUE EDUCATION. - Dr. Subhash Talukdar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Peace is a sense of happiness and a feeling of contentment within us and the outside forces amidst the pain. Peace is the symbol of civilized society. It is the blessing for mankind. Peace is the first requisite for laying the foundation of the world. Peace education is the education which creation of a non-explosive, non-oppressive and non-violent. Education promotes tolerance, understanding, and friendship among nations. The main aim of peace education is to build up a social order and to prepare values such as justice, compassion, equality, gender fairness, sharing for life with non violence. There is some need of peace education. The principles of peace education are – respect of life, reject the violence, sharing attitude with others, listen to understand, preserve the planet, re-discover the solidarity. Value education means in those educations a sense of humanism, a deep concern for the well being of others and the nation. Educational values mean those activities which are good, useful and valuable. Value based education promote peace in a society. Value oriented education leads the individual to realize his potential and to achieve something higher in life. It involves teaching of values and removes the narrow and selfish ideas. There are two views of value education. Firstly, values depend upon personal ideas and experiences. Secondly, values are inherent in objects and activities in accordance to their qualities and attributes. Educational institutions can inculcate value education through the following ways and means. These are –development of positive social attitudes, development of moral qualities, humanizing effect, develops co-operation and fellow-feeling, development of democratic qualities. Therefore, we can say peace and value education has great importance. All Post-independence Commissions and committees on education in India have recommended value education. It gives us moral lessons and various other activities in the School. In this paper an attempt has been made initiative towards the peace and value education and need of peace and value education.